Hubungan Aktivitas Komunikasi Electronic Word Of Mouth dan Citra Merek dengan Loyalitas Pelanggan IndiHome - Radika Oktavianti, Dina; Pradekso, Tandiyo; Setyabudi, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Since the COVID-19 pandemic, majority of teaching and learning activities have been conducted online. Batam itself also follows this policy, so that the demand for home internet services highly increases. IndiHome is one of the largest internet service providers in Batam. Unfortunately, IndiHome Batam customers are indicated to have a high tendency to switch providers. In addition, since August 2020 IndiHome has received negative attention on social media because of its declining internet quality. Conditions like this certainly have the potential to reduce the public's positive perception of IndiHome, whereas a positive perception of the brand can encourage consumer loyalty. IndiHome is the first and largest provider that has many regular customers in Batam, but the negative spotlight about IndiHome was entered and discussed by the Batam community in regional forums. The spread of this negative spotlight can certainly affect loyalty, because negative WOM can gradually encourage consumers to become disloyal to the product or service of the related brand. This research aims to determine the relationship between electronic word of mouth communication activities and brand image with IndiHome customer loyalty in Batam. There is two theory used in this research which is social cognitive theory and brand image theory. The test was carried out using the Kendall tau b correlation analysis test with a non-probability sampling technique. This study uses a sample of 70 people with characteristics aged 17-34 years, are IndiHome customers, domiciled in Batam, and actively use social media. The results showed that eWOM communication activity (X1) with customer loyalty IndiHome (Y) obtained a significance value of 0.870 which means it is not significant. Furthermore, brand image (X2) with IndiHome customer loyalty (Y) obtained a significance value of 0.000 which means it is very significant with a correlation coefficient of 0.540 and a positive relationship direction.